Analysis of Prophylactic Antibiotic Administration in BPJS-Covered Patients Undergoing Caesarean Section at Husada Utama Hospital, Surabaya - Alfarendra, Muhammad Daffa; Indrayanti, Mufida; Yulia, Rika; Herawati, Fauna (Journal of Maternal and Child Health, 2024)
Background: Considering the importance of the rational use of antibiotics to prevent the development of antibiotic resistance, especially in surgical patients who are at risk of developing Surgical Site Infections (SSI). A study will be conducted to evaluate the use of antibiotics in caesarean section patients at Husada Utama Hospital Surabaya. Subjects and Method: This study uses a descriptive observational research design with a retrospective data collection approach on patients who underwent either emergency or elective caesarean section (CS) on January – may 2024 at Husada Utama Hospital Surabaya. The variables in this study are the antibiotic use patterns of CS patients, which include the type of antibiotics used, the antibiotic dosage, the duration of antibiotic administration, the amount of antibiotic use measured by the DDD/100 bed days method and DU90%, the appropriateness of antibiotic use according to the national formulary and hospital antibiotic guidelines, the response time for CS surgery, and the risk of developing surgical site infection (SSI). The sample for this study consisted of patients who underwent either emergency or elective CS surgery at the Husada Utama Hospital Surabaya from January to May 2024. Results: From January to May 2024, 69 samples were analysed. These included 65 patients undergoing elective caesarean sections and 4 patients undergoing emergency caesarean sections with a response time of <30 minutes. The antibiotics used were cefazolin 2 g and ceftriaxone 1 g, administered intravenously over 30-60 minutes. Antibiotic consumption was measured using the DDD/100 bed days method and DU 90% segment. The amount of cefazolin used was 26.50 DDD/100 bed days and the amount of ceftriaxone used was 0.96 DDD/100 bed days. Cefazolin was the most commonly used antibiotic in all types of surgery, accounting for 95.65% of the DU 90% segment. Antibiotic use 95.65% was in accordance with PPAB guidelines and Ministry of Health regulations in terms of type, dosage and route of administration. There were no surgical site infections during the study period. Conclusion: Ninety five percent of antibiotic use in caesarean section patients in the hospital is in accordance with the type of antibiotic recommended in the antibiotic use guidelines, which is cefazolin. The use of the broad-spectrum antibiotic ceftriaxone is 0.96 DDD/100 bed days. The programme to control antimicrobial resistance in the obstetrics and gynaecology unit, especially regarding the prophylactic use of antibiotics, is effective.